2013
DOI: 10.1039/c3cc44947e
|View full text |Cite
|
Sign up to set email alerts
|

Calcium carbonate biomineralization utilizing a multifunctional β-sheet peptide template

Abstract: We designed a novel multifunctional β-sheet peptide template for calcium carbonate mineralization. The template self-supplies the mineral source, a carbonate ion, by hydrolysis of urea, and regulates the crystal phase and morphology of the obtained calcium carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Xu et al revealed that control of morphology and size of nanostructures were observed by using a self-assembling peptide template. In addition, our group previously showed that the morphologies of inorganic materials are controlled on a self-assembling peptide template [30,31,32,33] and elucidated that the secondary structures of peptides have a great impact on the resulting particles.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al revealed that control of morphology and size of nanostructures were observed by using a self-assembling peptide template. In addition, our group previously showed that the morphologies of inorganic materials are controlled on a self-assembling peptide template [30,31,32,33] and elucidated that the secondary structures of peptides have a great impact on the resulting particles.…”
Section: Introductionmentioning
confidence: 99%
“…One extensively study is the biomineralization of highly ordered biosilica from alkoxysilane such as tetramethoxysilane (TMOS) and tetraethoxysilane (TEOS) using biomolecules (e.g., peptides, proteins, and nucleic acids); this system offers precise control the nanostructure of the obtained inorganic material [26][27][28][29][30]. In addition, polyamines and polypeptides (like poly-L -lysine) can catalyze silicic acid deposition [31][32][33][34][35]. Interestingly, Tomczak et al [36] determined that poly-L -lysine with an α-helix conformation precipitated to form hexagonal silica platelets.…”
Section: Introductionmentioning
confidence: 99%
“…However, this involves many steps in the process of their fabrication. With this in mind, in our previous study, we focused on biomineralization, which involves the fabrication of functional materials via a single process . Biomineralization controls the morphology, crystal phase, and functionality of mineralized inorganic matters (e.g., calcium carbonate, calcium phosphate, and silica) via the nanostructure of the organic template surface (e.g., protein or polysaccharide) .…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, in our previous study,w ef ocused on biomineralization, which involves the fabrication of functional materials via as ingle process. [13][14][15][16][17][18][19][20][21] Biomineralization controlst he morphology,c rystal phase, and functionality of mineralized inorganic matters( e.g.,c alcium carbonate, calcium phosphate, and silica) via the nanostructure of the organic template surface (e.g.,p rotein or polysaccharide). [22] Collagen is at ypical organic template that has gained interesti ns everal fields of research asafunctional material with aw ide variety of functions.…”
Section: Introductionmentioning
confidence: 99%